Preparation method of zinc oxide-aluminum oxide ceramic bone repair scaffold
Through 3D printing and nano-zinc oxide sol vacuum pressure infiltration technology, the filling spacing and laser power gradient are dynamically adjusted, longitudinal through-hole channels are designed, and vacuum pressure infiltration parameters are optimized. This solves the problem of insufficient blood transport in traditional bone repair scaffolds, improves the antibacterial properties, hydrophilicity and penetration efficiency of zinc oxide-alumina ceramic bone repair scaffolds, and reduces bone central necrosis and repair failure.
Patent Information
- Application Number
- CN202510828488.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-06-19
AI Technical Summary
Traditional bone repair scaffold preparation methods make it difficult to accurately design the appearance and internal microstructure, resulting in insufficient blood transport, often causing central bone necrosis and repair failure.
3D printing technology is combined with selective laser sintering and vacuum pressure infiltration of nano-zinc oxide sol. By dynamically adjusting the filling spacing and laser power gradient, longitudinal through-holes are designed. The vacuum pressure infiltration parameters are optimized using the dynamic optimization algorithm to prepare zinc oxide-alumina ceramic bone repair scaffolds.
The zinc oxide-alumina ceramic bone repair scaffold has achieved a synergistic improvement in antibacterial properties, hydrophilicity and penetration efficiency, thereby improving blood transport efficiency and reducing central bone necrosis and repair failure.
Smart Images

Figure CN120682021A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a method for preparing a zinc oxide-aluminum oxide ceramic bone repair scaffold. Background Art
[0002] Bone defects caused by tumors, infections, trauma, etc. are common clinical diseases, characterized by large numbers and complex injuries, and seriously affect the quality of life of patients. The bone repair materials currently used in clinical practice are mainly metal materials, biopolymer materials, artificial synthetic inorganic materials and their composites. Among them, alumina bioceramics are similar to the inorganic components and spatial three-dimensional structure of bone tissue, and have good biocompatibility and osteoconductivity. They can combine well with bone tissue in the body to achieve bone defect repair. Metal oxides such as zinc oxide can give alumina ceramic bone repair scaffolds more powerful antibacterial ability through the dual pathways of releasing metal ions and generating reactive oxygen species, thereby promoting the bone repair process. Alumina bioceramic scaffolds are widely used as bioactive materials, and zinc oxide-alumina bioceramics are a research hotspot in the field of bone repair biomaterials today.
[0003] The preparation methods of bone repair scaffolds mainly include foaming, particle leaching and freeze-drying. Among them, the foaming method forms a porous structure by impregnating ceramic slurry into an organic foam template and sintering it at high temperature. The particle leaching method uses a soluble pore-forming agent (such as NaCl particles) to mix with ceramic powder, and then leach the pore-forming agent after sintering to form pores.
[0004] Traditional bone repair scaffold preparation methods make it difficult to accurately design the appearance and internal microstructure of the bone repair scaffold, resulting in the inability to achieve blood transportation inside the scaffold and unable to provide sufficient blood supply to the middle section of large bone defects, often leading to problems such as central bone necrosis and repair failure. Summary of the Invention
[0005] In response to the problems in the related art, the present invention provides a method for preparing a zinc oxide-aluminum oxide ceramic bone repair scaffold to overcome the technical problems existing in the existing related art.
[0006] To solve the above technical problems, the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a zinc oxide-aluminum oxide ceramic bone repair scaffold, comprising the following steps:
[0008] S1. Preparation of 3D printing powder: weighing alumina granulation powder and phenolic resin powder according to a proportion, mixing the alumina granulation powder and phenolic resin powder to obtain 3D printing composite powder;
[0009] S2, forming: preparing an alumina ceramic body by subjecting the 3D printed composite powder to a selective laser sintering device;
[0010] S3, degreasing and sintering: drying the alumina ceramic body to obtain a dried ceramic body, degreasing and sintering the dried ceramic body, and cooling to obtain an alumina preform;
[0011] S4. Body infiltration: vacuum pressure infiltration is performed on the alumina preform using nano zinc oxide sol, and the dynamic optimization algorithm is introduced to optimize the vacuum pressure infiltration parameters to obtain a zinc oxide-alumina ceramic bone repair scaffold.
[0012] Preferably, the weighing of alumina granulated powder and phenolic resin powder in proportion and mixing of the alumina granulated powder and phenolic resin powder comprises the following steps:
[0013] 20-75 micron nearly spherical alumina powder and phenolic resin are selected, and after drying, alumina granulation powder and phenolic resin powder are obtained. The alumina granulation powder and phenolic resin powder are weighed according to the proportion, and the alumina granulation powder and phenolic resin powder are mixed to obtain 3D printing composite powder.
[0014] Preferably, the alumina granulated powder and the phenolic resin powder are weighed in a mass ratio of 0.92:0.08.
[0015] Preferably, the step of subjecting the 3D printed composite powder to selective laser sintering equipment comprises the following steps:
[0016] The 3D printed composite powder was passed through a selective laser sintering device, wherein the operating parameters of the selective laser sintering device were a preheating temperature of 55° C., a layer thickness of 0.18±0.01 mm, a filling speed of 3850±100 mm / s, a filling power of 18 W, a contour speed of 2000±100 mm / s, and a contour power of 10 W;
[0017] A gradient filling strategy was adopted to set longitudinal through-holes along the long axis of the bone in the selective laser sintering equipment, maintain the pore size at 200-500 microns, and adjust the gradient distribution of the hole spacing to obtain an alumina ceramic green body.
[0018] Preferably, the degreasing and sintering of the dried ceramic body comprises the following steps:
[0019] The alumina ceramic body is dried to obtain a dried ceramic body, and the dried ceramic body is degreased to obtain a degreased ceramic body; a multi-stage sintering method is then used for sintering. After the sintering, the temperature is lowered to 1100° C. at a rate of 5° C.±1° C. / min, and the alumina preform is obtained by cooling.
[0020] Preferably, the degreasing treatment is carried out under nitrogen protection, with the temperature being raised to 300°C at 1°C±0.1°C / min, kept warm for 2 hours, and then raised to 600°C at 2°C±0.2°C / min, kept warm for 30 minutes to complete the degreasing treatment.
[0021] Preferably, the multi-stage sintering method is used for sintering, which comprises the following steps:
[0022] During the first stage of sintering, the degreased ceramic body is kept at 600°C for 30 minutes; during the second stage of sintering, the temperature is increased to 1250°C at 8°C±1°C / min; during the third stage of sintering, the temperature is increased to 1300-1500°C at 2.5°C±0.5°C / min and kept at this temperature for 3 hours to complete the sintering process.
[0023] Preferably, the vacuum pressure infiltration of the alumina preform using the nano zinc oxide sol comprises the following steps:
[0024] Nano zinc oxide sol is prepared, and the aluminum oxide preform is vacuum pressure infiltrated with the nano zinc oxide sol. The aluminum oxide preform is placed in a vacuum pressure infiltration device and infiltrated into the nano zinc oxide sol. The vacuum pressure infiltration parameters are as follows: vacuum negative pressure of 0.06-0.10 MPa, maintained for 1-5 minutes, and then nitrogen is introduced to increase the pressure to 0.10-0.20 MPa and maintained for 1-5 minutes.
[0025] Preferably, the introduction of the dynamic optimization algorithm to optimize the vacuum pressure infiltration parameters includes the following steps:
[0026] The antibacterial rate, contact angle, and penetration rate of zinc oxide-alumina ceramic bone repair scaffolds were measured, and an objective function was established based on maximum anti-inflammatory and sterilization performance and superhydrophilic properties.
[0027] The vacuum pressure infiltration parameters include vacuum negative pressure, pressurization pressure, infiltration time and number of cycles, which constitute a vacuum pressure infiltration parameter combination; the objective function is used as a fitness function, and the process of finding the optimal fitness function value is regarded as the process of finding the optimal vacuum pressure infiltration parameter combination;
[0028] A search space is set, in which there is an oat population, and each oat individual in the oat population is regarded as a vacuum pressure infiltration parameter combination;
[0029] Initialize the oat population and calculate the biological parameters of the oat population;
[0030] The oat population enters the exploration phase. After the oats fall, they spread. The positions of individual oats in the oat population are updated. The fitness function values corresponding to the individual oats in the oat population are calculated to obtain the current vacuum pressure infiltration parameter combination.
[0031] The oat population enters the development phase, and the current vacuum pressure infiltration parameter combination is updated by simulating the propagation process;
[0032] When the oat population does not encounter any obstacles during its propagation, the Lévy flight and tumbling mechanism is introduced to update the position of individual oats according to the biological parameters of the oat population.
[0033] When the oat population encounters an obstacle during its propagation, the projectile motion model is introduced to update the individual oat positions again;
[0034] Until the current number of iterations reaches the maximum number of iterations, the iteration is stopped to obtain a final oat population; the oat individual corresponding to the best fitness function value is found in the final oat population to obtain the optimized vacuum pressure infiltration parameters.
[0035] Preferably, the step of obtaining the zinc oxide-aluminum oxide ceramic bone repair scaffold comprises the following steps:
[0036] The optimized vacuum pressure infiltration parameters include optimized vacuum negative pressure, optimized pressurization pressure, optimized infiltration time and optimized number of cycles. The alumina preform is vacuum pressure infiltrated according to the optimized vacuum pressure infiltration parameters to obtain an infiltrated repair scaffold, which is then dried and low-temperature cured to obtain a zinc oxide-alumina ceramic bone repair scaffold.
[0037] The present invention has the following beneficial effects:
[0038] 1. This invention achieves an optimal balance of material properties by selecting alumina powder and phenolic resin in a mass ratio of 92:8, ensuring fluidity while improving uniformity. It uses mechanical mixing and drying to avoid the generation of pores during subsequent high-temperature molding, thus solving the contradiction between strength and formability of 3D printing ceramic materials.
[0039] 2. This invention passes 3D printed composite powder through a selective laser sintering device, dynamically adjusts the filling spacing and laser power gradient, and achieves a gradient distribution of porosity from the center to the edge, effectively balancing mechanical strength and permeability. It is suitable for bone implants that meet the dual requirements of load-bearing and nutrient delivery, and introduces a longitudinal through-channel simulation design to simulate the natural trabecular bone structure, thereby improving blood transport efficiency.
[0040] 3. The invention reduces the defect rate of the alumina ceramic body by drying the alumina ceramic body and then degreasing and sintering it using a staged gradient temperature increase, which causes cracking or internal pore defects in the body. The entire process uses refined temperature control of the degreasing-sintering-cooling process, taking into account material properties, process efficiency and cost-effectiveness.
[0041] 4. The invention uses nano-zinc oxide sol to perform vacuum pressure infiltration on an alumina preform, and introduces a dynamic optimization algorithm to optimize the vacuum pressure infiltration parameters to prepare a zinc oxide-alumina ceramic bone repair scaffold; this method uses the dynamic optimization algorithm to find the optimal parameters, cleverly balancing global exploration and local development, and has better performance than traditional optimization algorithms; the antibacterial rate is used to quantify the anti-inflammatory and sterilization performance, and the contact angle and blood self-transport rate are used to quantify the super-hydrophilic performance, so that more nano-zinc oxide can enter the micropores, with better anti-inflammatory and sterilization effects, while driving rapid blood transport, reducing flow resistance, and greatly reducing problems such as bone center necrosis and repair failure, thereby achieving a synergistic improvement in the antibacterial properties, hydrophilicity and penetration efficiency of the zinc oxide-alumina ceramic bone repair scaffold.
[0042] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the invention. For ordinary technicians in this field, they can also obtain drawings based on these drawings without paying any creative work.
[0044] Figure 1 The present invention provides a schematic flow chart of a method for preparing a zinc oxide-aluminum oxide ceramic bone repair scaffold. DETAILED DESCRIPTION
[0045] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0046] In order to better introduce the technical solutions of the embodiments of the present invention, Figure 1 As shown, an embodiment of the present invention provides a method for preparing a zinc oxide-aluminum oxide ceramic bone repair scaffold, which specifically includes the following contents:
[0047] S1. Preparation of 3D printing powder: weighing alumina granulation powder and phenolic resin powder according to a proportion, mixing the alumina granulation powder and phenolic resin powder to obtain 3D printing composite powder;
[0048] Said S1 comprises the following steps:
[0049] S11. Select 20-75 micron nearly spherical alumina powder and phenolic resin, dry them at 150°C for 4 hours to obtain alumina granulation powder and phenolic resin powder, weigh the alumina granulation powder and phenolic resin powder in a mass ratio of 0.92:0.08, and mix the alumina granulation powder and phenolic resin powder by mechanical mixing. Keep mixing for 12 hours to obtain a 3D printing composite powder;
[0050] In this embodiment, alumina powder and phenolic resin powder are selected and mechanically mixed to obtain 3D printing composite powder; the use of near-spherical powder ensures fluidity while improving uniformity, and the drying treatment avoids the generation of pores during subsequent high-temperature molding. The mass ratio of 92:8 achieves the optimal balance of material properties, solving the contradiction between strength and formability of 3D printing ceramic materials; specifically, for example, near-spherical alumina powder (Al2O3 content ≥99.5%) with a particle size of 50 μm and phenolic resin are placed in a vacuum drying oven at 150°C for 4 hours, and 92 kg of alumina granulated powder and 8 kg of phenolic resin powder (pyrolytic carbon residue rate 45%) are accurately weighed and loaded into a three-dimensional mixer together; the equipment speed is set to 25 rpm, and mechanical mixing is performed under a nitrogen protection environment for 12 hours to obtain a uniform composite powder with a fluidity index <35°;
[0051] S2, forming: preparing an alumina ceramic body by subjecting the 3D printed composite powder to a selective laser sintering device;
[0052] The S2 comprises the following steps:
[0053] S21. Pass the 3D printed composite powder through a selective laser sintering device, wherein the operating parameters of the selective laser sintering device are a preheating temperature of 55° C., a layer thickness of 0.18±0.01 mm, a filling speed of 3850±100 mm / s, a filling power of 18 W, a contour speed of 2000±100 mm / s, and a contour power of 10 W;
[0054] S22, using a gradient filling strategy, providing longitudinal through-holes along the long axis of the bone in a selective laser sintering device, maintaining a pore diameter of 200-500 μm, and adjusting the gradient distribution of the pore spacing to obtain an alumina ceramic body;
[0055] In this embodiment, the 3D printed composite powder is passed through a selective laser sintering device to prepare an alumina ceramic body; the process achieves a gradient distribution of porosity from the center to the edge by dynamically adjusting the filling spacing and the laser power gradient; specifically, for example, the filling parameters are: speed 3850 mm / s, laser power 18 W, and the profile parameters are: speed 2000 mm / s, laser power 10 W; a gradient filling strategy is used for three-dimensional molding: a longitudinal through-hole network is designed along the long axis of the bone, and the hole diameter is controlled within the range of 200-500 μm. By dynamically adjusting the laser scanning path, a gradient distribution of the hole spacing is achieved (0.3 mm in the center area). The interlayer rotation angle is set to 67° to avoid anisotropic defects. The porosity of the alumina ceramic green body sample was measured by helium pycnometry to be 38±2%, and micro-CT analysis showed that the through-hole ratio was greater than 85% (effectively balancing mechanical strength and permeability). The axial compressive strength tested according to the ISO13314 standard was greater than 120MPa (high mechanical properties), and the surface roughness measured by white light interferometry was less than 15μm (improving molding efficiency). The entire process is suitable for bone implants requiring both load-bearing and nutrient delivery. The introduction of a longitudinal through-hole simulation design simulates the natural trabecular bone structure, improving blood transport efficiency.
[0056] S3, degreasing and sintering: drying the alumina ceramic body to obtain a dried ceramic body, degreasing and sintering the dried ceramic body, and cooling to obtain an alumina preform;
[0057] The S3 includes the following steps:
[0058] S31, drying the alumina ceramic body to obtain a dried ceramic body, and degreasing the dried ceramic body. Under nitrogen protection, heating the body to 300° C. at a rate of 1° C.±0.1° C. / min, holding the temperature for 2 hours, and then heating the body to 600° C. at a rate of 2° C.±0.2° C. / min, holding the temperature for 30 minutes to complete the degreasing process and obtain a degreased ceramic body. Then, sintering the body by a multi-stage sintering method, the specific steps are as follows:
[0059] S311, during the first stage sintering, the degreased ceramic body is kept at 600° C. for 30 minutes; during the second stage sintering, the temperature is increased to 1250° C. at a rate of 8° C.±1° C. / min; during the third stage sintering, the temperature is increased to a sintering temperature of 1300-1500° C. at a rate of 2.5° C. / min and kept at this temperature for 3 hours to complete the sintering process;
[0060] S32, after sintering, cooling to 1100° C. at a rate of 5° C.±1° C. / min, and cooling to obtain an alumina preform;
[0061] In this embodiment, the alumina ceramic body is dried, degreased and sintered, and then cooled to obtain an alumina preform; the method adopts a staged gradient heating method, which reduces the cracking or internal pore defects of the body and reduces the body defect rate. The entire process uses refined temperature control of the degreasing-sintering-cooling process, taking into account material properties, process efficiency and cost-effectiveness; specifically, for example, the dried alumina ceramic body is placed in a nitrogen protective atmosphere, and gradient heating degreasing is performed to obtain a degreased ceramic body; a multi-stage sintering method is adopted: the first stage ( Pre-sintering: The degreased ceramic body is kept at 600°C for 30 minutes; the second stage (transition sintering): the temperature is increased from 600°C to 1250°C at a rate of 8°C±1°C / min; the third stage (final sintering): the temperature is increased from 1250°C to the target temperature (the specific value is selected in the range of 1300-1500°C) at a rate of 2.5°C±0.5°C / min, and kept at this temperature for 3 hours; after sintering, the temperature is programmed to 1100°C at a rate of 5°C / min, and then cooled to room temperature in the furnace to finally obtain a densified alumina preform;
[0062] S4. Body infiltration: vacuum pressure infiltration of the alumina preform using nano zinc oxide sol, and optimizing the vacuum pressure infiltration parameters using a dynamic optimization algorithm to obtain a zinc oxide-alumina ceramic bone repair scaffold;
[0063] The S4 comprises the following steps:
[0064] S41, using zinc nitrate as a precursor and ethanol as a solvent, adjusting the pH to 9-10 with ammonia water, stirring in a water bath at 60° C. for 4 hours to prepare a nano zinc oxide sol;
[0065] S42, vacuum pressure infiltration of the alumina preform with the nano zinc oxide sol, placing the alumina preform in a vacuum pressure infiltration apparatus and infiltrating it into the nano zinc oxide sol, wherein the vacuum pressure infiltration parameters are: a vacuum negative pressure of 0.06-0.10 MPa, maintained for 1-5 minutes, and then introducing nitrogen to increase the pressure to 0.10-0.20 MPa, and maintained for 1-5 minutes;
[0066] S43, the vacuum pressure impregnation parameters include vacuum negative pressure, pressurization pressure, impregnation time and number of cycles, which constitute a vacuum pressure impregnation parameter combination, and the vacuum pressure impregnation parameters are optimized using the dynamic wheat optimization algorithm to obtain the optimized vacuum pressure impregnation parameters. The specific steps are as follows:
[0067] S431. Measure the antibacterial rate, contact angle, and penetration rate of the zinc oxide-alumina ceramic bone repair scaffold. Based on the maximum anti-inflammatory and sterilization performance and superhydrophilic properties, establish the following objective function:
[0068]
[0069] Wherein, F represents the objective function, α1 represents the antibacterial rate of the zinc oxide-alumina ceramic bone repair scaffold, α2 represents the contact angle of the zinc oxide-alumina ceramic bone repair scaffold, α3 represents the penetration rate of the zinc oxide-alumina ceramic bone repair scaffold, ω1, ω2 and ω3 represent weight coefficients, and the sum of the weight coefficients is guaranteed to be 1;
[0070] S432, taking the objective function as a fitness function, and regarding the process of finding the optimal fitness function value as the process of finding the optimal vacuum pressure infiltration parameter combination;
[0071] Set a search space, in which there is an oat population, set the number of oat populations to p, the dimension of oat populations to q, and regard each oat individual in the oat population as a vacuum pressure infiltration parameter combination;
[0072] Initialize the oat population, set d to represent a random number between the interval [0, 1], the current number of iterations to t, the maximum number of iterations to T, and then calculate the biological parameters of the oat population. The biological parameters of the oat population include seed quality Main awn length Eccentric rotation coefficient Explore and develop smoothing coefficients
[0073] S433, the oat population enters the exploration phase, and the oats are propagated after being dropped. The upper bound of the search space is set to l, and d1 represents a random number between the interval [0, q]. Indicates OR operation, at this time the oat position update coefficient Update the oat individuals in the oat population and set the position of the e-th oat individual at the t-th iteration to C e (t), the average position of the oat population at the tth iteration is The optimal position of the oat population at the tth iteration is C best (t), when the remainder of e and p / 10 is 0, the position of the e-th oat individual at the t+1th iteration is When the remainder of e and p / 10 is 1, then C e (t+1)=C best (t)+β, otherwise C e (t+1)=C e (t) + β; at this time, the fitness function value corresponding to the oat individual in the oat population is calculated to obtain the current vacuum pressure infiltration parameter combination;
[0074] S434, the oat population enters the development stage, simulating the propagation process and then updating the current vacuum pressure infiltration parameter combination. The oat population in the propagation process includes the situation of encountering obstacles and the situation of encountering obstacles; when there is no obstacle, the Lévy flight and tumbling mechanism is introduced to update the position of the oat individual, and the torsion coefficient Set the twist matrix A, where the elements in the twist matrix are random numbers between the interval [-χ, χ], and the eccentric rotation coefficient Assuming the Levy flight coefficient is Levy(q), we get
[0075] When encountering an obstacle, the projectile motion model is introduced to update the position of the e-th oat individual at the t-th iteration again. At this time, all stages are completed and the next generation of oat population is generated. Until the current number of iterations reaches the maximum number of iterations, the iteration is stopped to obtain the final oat population; the oat individual corresponding to the best fitness function value is found in the final oat population to obtain the optimized vacuum pressure infiltration parameters;
[0076] S44, the optimized vacuum pressure infiltration parameters include the optimized vacuum negative pressure, the optimized pressurization pressure, the optimized infiltration time, and the optimized number of cycles, and the alumina preform is vacuum pressure infiltrated according to the optimized vacuum pressure infiltration parameters to obtain an infiltrated repair scaffold, which is then dried and low-temperature cured to obtain a zinc oxide-alumina ceramic bone repair scaffold;
[0077] In this embodiment, nano zinc oxide sol is used to perform vacuum pressure infiltration on an alumina preform, and a dynamic wheat optimization algorithm is introduced to optimize the vacuum pressure infiltration parameters to obtain optimized vacuum pressure infiltration parameters and prepare a zinc oxide-alumina ceramic bone repair scaffold; this method uses the dynamic wheat optimization algorithm to find the optimal parameters, and by simulating the "rolling-bouncing" propagation mechanism of oat seeds, it cleverly takes into account both global exploration (avoiding local optimality) and local development (rapid convergence), and its performance is better than that of traditional optimization algorithms; and the antibacterial rate is used to quantify the anti-inflammatory and sterilization performance, and the contact angle (less than 10° is super-hydrophilic) and the blood self-transport rate are used to quantify the super-hydrophilic performance, so that more nano zinc oxide can enter the micropores, and has better anti-inflammatory and sterilization effects, while driving It can promote the rapid transport of blood, reduce flow resistance, greatly reduce problems such as bone center necrosis and repair failure, and realize the synergistic improvement of zinc oxide-alumina ceramic bone repair scaffold in antibacterial property, hydrophilicity and penetration efficiency; specifically, for example, precursor: zinc nitrate (concentration 0.1 mol / L), solvent: anhydrous ethanol, mixed in a volume ratio of 1:3, and then ammonia water was added to adjust the pH to 9.5, and stirred in a 60°C water bath for 4 hours to obtain a uniform nano zinc oxide sol; the antibacterial rate target is guaranteed to be ≥90%, the contact angle target is ≤10°, and the penetration rate target is ≥8μL / min; in the embodiment process, the relationship between clinical outcomes (such as infection rate, healing time) and performance indicators is established by regression analysis of past case data , reversely deducing the optimal weights, we obtain clinical scenario A (high infection risk): priority is given to antibacterial activity, with weights assigned as: antibacterial rate (50%), hydrophilicity (30%), and permeation rate (20%), with weight coefficients ω1, ω2, and ω3 of 0.5, 0.3, and 0.2, respectively. Scenario B (rapid healing requirement): priority is given to hydrophilicity and blood permeation, with weights assigned as: antibacterial rate (30%), hydrophilicity (40%), and permeation rate (30%), with weight coefficients ω1, ω2, and ω3 of 0.3, 0.4, and 0.3, respectively. Scenario C (balanced performance): default weight assignment is: antibacterial rate (40%), hydrophilicity (35%), and permeation rate (25%), with weight coefficients ω1, ω2, and ω3 of 0, respectively. 4, 0.35 and 0.25; for example, according to the priority inhibition, the weight coefficients are set to 0.5, 0.3 and 0.2 respectively; for example, the oat population size is set to 50, the dimension is 4 (corresponding to 4 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% of iterations, the population updates the parameter combination through the average position and the optimal position, and introduces the Levy flight adjustment parameters to avoid local optimality. When encountering obstacles, the projectile motion model is introduced to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: vacuum negative pressure: 0.095MPa (maintained for 2min), pressurization pressure: 0.18MPa (maintained for 2min), and number of cycles: 3 times.
[0078] The following is a detailed description with reference to specific embodiments:
[0079] Example 1:
[0080] S1. Preparation of 3D printing powder: weighing alumina granulation powder and phenolic resin powder according to a proportion, mixing the alumina granulation powder and phenolic resin powder to obtain 3D printing composite powder;
[0081] Specifically, the S1 includes the following steps:
[0082] S11. Take nearly spherical alumina powder (Al2O3 content ≥99.5%) with a particle size of 50 μm and phenolic resin, place them in a vacuum drying oven at 150°C for 4 hours, and accurately weigh 92 kg of alumina granulation powder and 8 kg of phenolic resin powder (pyrolytic carbon residue rate 45%), and load them together into a three-dimensional mixer; set the equipment speed to 25 rpm, and perform mechanical mixing under a nitrogen protection environment for 12 hours to obtain a uniform composite powder with a flowability index <35°;
[0083] S2, forming: preparing an alumina ceramic body by subjecting the 3D printed composite powder to a selective laser sintering device;
[0084] Specifically, the S2 includes the following steps:
[0085] S21. Pass the 3D printed composite powder through a selective laser sintering device, wherein the operating parameters of the selective laser sintering device are a preheating temperature of 55° C., a layer thickness of 0.18±0.01 mm, a filling speed of 3850±100 mm / s, a filling power of 18 W, a contour speed of 2000±100 mm / s, and a contour power of 10 W;
[0086] S22, using a gradient filling strategy, providing longitudinal through-holes along the long axis of the bone in a selective laser sintering device, maintaining a pore diameter of 200-500 μm, and adjusting the gradient distribution of the pore spacing to obtain an alumina ceramic body;
[0087] Specifically, the filling parameters were: speed 3850 mm / s, laser power 18 W, and contour parameters: speed 2000 mm / s, laser power 10 W. A gradient filling strategy was used for three-dimensional forming: a longitudinal through-hole network was designed along the long axis of the bone, with the hole diameter controlled within the range of 200-500 μm. By dynamically adjusting the laser scanning path, a gradient distribution of the hole spacing was achieved (0.3 mm spacing in the central area and 0.7 mm spacing in the peripheral area), and the interlayer rotation angle was set to 67°. For the alumina ceramic green body sample, the porosity was measured to be 38±2% using the helium pycnometry method, and the proportion of through-holes was >85% using micro-CT analysis. The axial compressive strength was >120 MPa according to the ISO13314 standard, and the surface roughness was <15 μm using white light interferometry.
[0088] S3, degreasing and sintering: drying the alumina ceramic body to obtain a dried ceramic body, degreasing and sintering the dried ceramic body, and cooling to obtain an alumina preform;
[0089] Specifically, S3 includes the following steps:
[0090] S31, drying the alumina ceramic body to obtain a dried ceramic body, and degreasing the dried ceramic body. Under nitrogen protection, heating the body to 300° C. at a rate of 1° C.±0.1° C. / min, holding the temperature for 2 hours, and then heating the body to 600° C. at a rate of 2° C.±0.2° C. / min, holding the temperature for 30 minutes to complete the degreasing process and obtain a degreased ceramic body. Then, sintering the body by a multi-stage sintering method, the specific steps are as follows:
[0091] S311, during the first stage sintering, the degreased ceramic body is kept at 600° C. for 30 minutes; during the second stage sintering, the temperature is increased to 1250° C. at a rate of 8° C.±1° C. / min; during the third stage sintering, the temperature is increased to a sintering temperature of 1300-1500° C. at a rate of 2.5° C. / min and kept at this temperature for 3 hours to complete the sintering process;
[0092] S32, after sintering, cooling to 1100° C. at a rate of 5° C.±1° C. / min, and cooling to obtain an alumina preform;
[0093] S4. Body infiltration: vacuum pressure infiltration of the alumina preform using nano zinc oxide sol, and optimizing the vacuum pressure infiltration parameters using a dynamic optimization algorithm to obtain a zinc oxide-alumina ceramic bone repair scaffold;
[0094] Specifically, the S4 includes the following steps:
[0095] S41, using zinc nitrate as a precursor and ethanol as a solvent, adjusting the pH to 9-10 with ammonia water, stirring in a water bath at 60° C. for 4 hours to prepare a nano zinc oxide sol;
[0096] S42, vacuum pressure infiltration of the alumina preform with the nano zinc oxide sol, placing the alumina preform in a vacuum pressure infiltration apparatus and infiltrating it into the nano zinc oxide sol, wherein the vacuum pressure infiltration parameters are: a vacuum negative pressure of 0.06-0.10 MPa, maintained for 1-5 minutes, and then introducing nitrogen to increase the pressure to 0.10-0.20 MPa, and maintained for 1-5 minutes;
[0097] S43, the vacuum pressure impregnation parameters include vacuum negative pressure, pressurization pressure, impregnation time and number of cycles, which constitute a vacuum pressure impregnation parameter combination, and the vacuum pressure impregnation parameters are optimized using the dynamic wheat optimization algorithm to obtain the optimized vacuum pressure impregnation parameters. The specific steps are as follows:
[0098] S431. Measure the antibacterial rate, contact angle, and penetration rate of the zinc oxide-alumina ceramic bone repair scaffold. Based on the maximum anti-inflammatory and sterilization performance and superhydrophilic properties, establish the following objective function:
[0099]
[0100] Wherein, F represents the objective function, α1 represents the antibacterial rate of the zinc oxide-alumina ceramic bone repair scaffold, α2 represents the contact angle of the zinc oxide-alumina ceramic bone repair scaffold, α3 represents the penetration rate of the zinc oxide-alumina ceramic bone repair scaffold, ω1, ω2 and ω3 represent weight coefficients;
[0101] S432, taking the objective function as a fitness function, and regarding the process of finding the optimal fitness function value as the process of finding the optimal vacuum pressure infiltration parameter combination;
[0102] Set a search space, in which there is an oat population, set the number of oat populations to p, the dimension of oat populations to q, and regard each oat individual in the oat population as a vacuum pressure infiltration parameter combination;
[0103] Initialize the oat population, set d to represent a random number between the interval [0, 1], the current number of iterations to t, the maximum number of iterations to T, and then calculate the biological parameters of the oat population. The biological parameters of the oat population include seed quality Main awn length Eccentric rotation coefficient Explore and develop smoothing coefficients
[0104] S433, the oat population enters the exploration phase, and the oats are propagated after being dropped. The upper bound of the search space is set to l, and d1 represents a random number between the interval [0, q]. Indicates OR operation, at this time the oat position update coefficient Update the oat individuals in the oat population and set the position of the e-th oat individual at the t-th iteration to C e (t), the average position of the oat population at the tth iteration is The optimal position of the oat population at the tth iteration is C best (t), when the remainder of e and p / 10 is 0, the position of the e-th oat individual at the t+1th iteration is When the remainder of e and p / 10 is 1, then C e(t+1)=C best (t)+β, otherwise C e (t+1)=C e (t) + β; at this time, the fitness function value corresponding to the oat individual in the oat population is calculated to obtain the current vacuum pressure infiltration parameter combination;
[0105] S434, the oat population enters the development stage, simulating the propagation process and then updating the current vacuum pressure infiltration parameter combination. The oat population in the propagation process includes the situation of encountering obstacles and the situation of encountering obstacles; when there is no obstacle, the Lévy flight and tumbling mechanism is introduced to update the position of the oat individual, and the torsion coefficient Set the twist matrix A, where the elements in the twist matrix are random numbers between the interval [-χ, χ], and the eccentric rotation coefficient Assuming the Levy flight coefficient is Levy(q), we get
[0106] When encountering an obstacle, the projectile motion model is introduced to update the position of the e-th oat individual at the t-th iteration again. At this time, all stages are completed and the next generation of oat population is generated. Until the current number of iterations reaches the maximum number of iterations, the iteration is stopped to obtain the final oat population; the oat individual corresponding to the best fitness function value is found in the final oat population to obtain the optimized vacuum pressure infiltration parameters;
[0107] S44, the optimized vacuum pressure infiltration parameters include the optimized vacuum negative pressure, the optimized pressurization pressure, the optimized infiltration time, and the optimized number of cycles, and the alumina preform is vacuum pressure infiltrated according to the optimized vacuum pressure infiltration parameters to obtain an infiltrated repair scaffold, which is then dried and low-temperature cured to obtain a zinc oxide-alumina ceramic bone repair scaffold;
[0108] Specifically, the precursor: zinc nitrate (concentration 0.1 mol / L), solvent: anhydrous ethanol, are mixed in a volume ratio of 1:3, and then ammonia water is added to adjust the pH to 9.5, and stirred in a 60°C water bath for 4 hours to obtain a uniform nano-zinc oxide sol; the antibacterial rate target is guaranteed to be ≥90%, the contact angle target is ≤10° (less than 10° is super hydrophilic), and the penetration rate target is ≥8μL / min; based on clinical scenario A (high risk of infection), the weight coefficients ω1, ω2 and ω3 are set according to the priority antibacterial effect, respectively. 0.5, 0.3 and 0.2; for example, the oat population is set to 50, and the dimension is 4 (corresponding to 4 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% of iterations, the population updates the parameter combination through the average position and the optimal position, and introduces Levy flight to adjust the parameters to avoid local optimality. When encountering obstacles, the projectile motion model is introduced to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: vacuum negative pressure: 0.095MPa (maintained for 2min), pressurization pressure: 0.18MPa (maintained for 2min), number of cycles: 3, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0109] Example 2:
[0110] On the basis of Example 1, the difference from Example 1 is that the vacuum negative pressure and the pressurization pressure are fixed, and the infiltration time and the number of cycles are optimized; specifically, the vacuum negative pressure is fixed to 0.06 MPa, the pressurization pressure is fixed to 0.10 MPa, the initial infiltration time is set to 2 minutes, and the initial number of cycles is set to 5 times; the oat population size is set to 50, the dimension is 2 (corresponding to 2 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% iterations, the population updates the parameter combination through the average position and the optimal position, and introduces the Levy flight adjustment parameters to avoid local optimality. When encountering obstacles, the projectile motion model is introduced to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: the infiltration time is 5 minutes, the number of cycles is 8 times, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0111] Example 3:
[0112] On the basis of Example 1, the difference from Example 1 is that the infiltration time is fixed, and the vacuum negative pressure, pressurization pressure and number of cycles are optimized; specifically, the infiltration time is fixed to 1 minute, the initial number of cycles is set to 5 times, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the oat population size is set to 50, the dimension is 3 (corresponding to 3 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% iterations, the population updates the parameter combination through the average position and the optimal position, introduces the Levy flight adjustment parameter to avoid local optimality, and when encountering obstacles, introduces the projectile motion model to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: the number of cycles is 8 times, the vacuum negative pressure is 0.10 MPa, and the pressurization pressure is 0.20 MPa, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0113] Example 4:
[0114] On the basis of Example 1, the difference from Example 1 is that the number of cycles is fixed, and the vacuum negative pressure, pressurization pressure and infiltration time are optimized; specifically, the number of cycles is fixed to 5 times, the initial infiltration time is set to 2 minutes, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the oat population size is set to 50, the dimension is 3 (corresponding to 3 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% of iterations, the population updates the parameter combination through the average position and the optimal position, introduces the Levy flight adjustment parameter to avoid local optimality, and when encountering obstacles, introduces the projectile motion model to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: the infiltration time is 5 minutes, the vacuum negative pressure is 0.095 MPa, and the pressurization pressure is 0.18 MPa, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0115] Example 5:
[0116] On the basis of Example 1, different from Example 1, the particle swarm optimization algorithm is used to optimize the number of cycles, vacuum negative pressure, pressurization pressure and infiltration time; specifically, the initial number of cycles is set to 5 times, the initial infiltration time is set to 2 minutes, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the number of particles is set to 50, the dimension is 4 (corresponding to 4 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; the particle velocity is updated, the linear decreasing inertia converges, and then the particle position is updated. The variable boundary adopts reflection boundary processing to avoid invalid solutions, and the inhibition rate, contact angle, and penetration rate are recorded until the maximum number of iterations is reached to obtain the optimal parameter combination: the number of cycles is 4 times, the infiltration time is 5 minutes, the vacuum negative pressure is 0.09 MPa, and the pressurization pressure is 0.18 MPa, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0117] Example 6:
[0118] On the basis of Example 1, the difference from Example 1 is that scenario B (rapid healing requirement) is selected: hydrophilicity and blood penetration are prioritized, and the weight distribution is: antibacterial rate (30%), hydrophilicity (40%), and penetration rate (30%), that is, the weight coefficients ω1, ω2, and ω3 are 0.3, 0.4, and 0.3, respectively; the initial number of cycles is set to 5 times, the initial infiltration time is set to 2 minutes, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the number of particles is set to 50, the dimension is 4 (corresponding to 4 vacuum pressure infiltrations parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% of iterations, the population updates the parameter combination through the average position and the optimal position, and introduces Levy flight to adjust the parameters to avoid local optimality. When encountering obstacles, the projectile motion model is introduced to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: vacuum negative pressure: 0.08MPa (maintained for 5min), pressurization pressure: 0.19MPa (maintained for 5min), number of cycles: 5 times, and the zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0119] Example 7:
[0120] On the basis of Example 1, the difference from Example 1 is that scenario C (balanced performance) is selected: the default weight distribution is: antibacterial rate (40%), hydrophilicity (35%), and penetration rate (25%), that is, the weight coefficients ω1, ω2, and ω3 are 0.4, 0.35, and 0.25 respectively; the initial number of cycles is set to 5 times, the initial infiltration time is set to 2 minutes, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the number of particles is set to 50, and the dimension is 4 (corresponding to 4 vacuum pressure infiltration parameters). The maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% of iterations, the population updates the parameter combination through the average position and the optimal position, and introduces Levy flight to adjust the parameters to avoid local optimality. When encountering obstacles, the projectile motion model is introduced to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: vacuum negative pressure: 0.09MPa (maintained for 5min), pressurization pressure: 0.20MPa (maintained for 5min), number of cycles: 5 times, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0121] Example 8:
[0122] On the basis of Example 1, the difference from Example 1 is that the weight coefficients ω1, ω2 and ω3 are randomly selected as 0.4, 0.4 and 0.2 respectively; the initial number of cycles is set to 5 times, the initial infiltration time is set to 2 minutes, the initial vacuum negative pressure is 0.06 MPa, and the initial pressurization pressure is 0.10 MPa; the number of particles is set to 50, the dimension is 4 (corresponding to 4 vacuum pressure infiltration parameters), the maximum number of iterations is 100, and each parameter is randomly generated within the range; in the first 20% iterations, the population updates the parameter combination through the average position and the optimal position, introduces the Levy flight adjustment parameter to avoid local optimality, and when encountering obstacles, introduces the projectile motion model to regenerate the parameters until the maximum number of iterations is reached to obtain the optimal parameter combination: vacuum negative pressure: 0.15 MPa (maintained for 7 minutes), pressurization pressure: 0.22 MPa (maintained for 7 minutes), number of cycles: 8 times, and a zinc oxide-alumina ceramic bone repair scaffold is obtained.
[0123] In the above Examples 1-8, the measurement methods for the antibacterial rate and hydrophilicity all adopted the rabbit bone test. The specific steps of the rabbit bone test are as follows:
[0124] The cytotoxicity, anti-inflammatory and antibacterial properties, osteoinduction, and blood transport capacity of ZAS (zinc oxide-alumina ceramic bone repair scaffold) were investigated using bone marrow mesenchymal stem cells from rabbit bone marrow blood. The main characteristics included cell morphology, cell activity, and proliferation.
[0125] Material grouping: Three groups of materials were prepared, namely blank group (cultured in culture medium without bone repair scaffold), control group (cultured in traditional ceramic scaffold), and experimental group (cultured in ZAS);
[0126] Blood collection: surgically remove the rabbit femur, cut the femoral head at both ends, and flush to obtain the rabbit femoral bone marrow blood;
[0127] Inoculation of cell fluid: In the experimental group, rabbit bone marrow blood was directly aspirated using ZAS. After aspirating the full amount of rabbit bone marrow blood, the cells were cultured in an incubator for 20 minutes (if more than 1 hour, the cells were taken out and a little culture medium was added every 20 minutes). The culture period was 7-21 days.
[0128] During the culture process, the three groups of materials were treated as follows:
[0129] Days 1, 3, and 7: CCK-8 cell activity assay;
[0130] One day in advance, cells were seeded into 96-well plates, with 5 replicate wells and four time groups of 12, 24, 36, and 48 hours.
[0131] When the cells cover about 70% of the bottom of the well, ZAS is added according to the set concentration gradient and a blank control is set;
[0132] After 12 / 24 / 36 / 48 h, ZAS of the corresponding time groups were removed, and 10 μl CCK-8 detection reagent was added to each well;
[0133] Use an enzyme-labeled instrument to perform the test, and draw a cell viability bar graph after reading the data;
[0134] Note: The cell suspension must be mixed well during inoculation to avoid cell sedimentation and inconsistent number of cells inoculated; the culture medium in the outermost circle of wells on the culture plate is more volatile. To reduce errors, it is recommended to add only culture medium without cells to the wells around the culture plate; when adding CCK-8, it is recommended to add it obliquely against the wall of the culture plate and not to insert it below the surface of the culture medium, as this will easily generate bubbles and interfere with the OD value; before measuring the absorbance value, make sure that there are no bubbles in each well, otherwise it will interfere with the measurement and the absorbance value will be abnormal. Please measure the absorbance value at 450nm. If there is no 450nm filter, you can use a 420-480nm filter; if you measure the absorbance value of cultured cells for multiple consecutive days, please keep the CCK-8 incubation time consistent each time to avoid deviations in the absorbance value due to different incubation times;
[0135] Day 7: Divide the experimental group into three groups;
[0136] The first group of materials was quenched in the middle and fixed with electron microscopy fixative. The material was then mounted on a sample stage and placed in a SEM for observation and selected area electron diffraction analysis. Cell morphology was observed for cell density, cell shape, cell floating, and other morphological characteristics. Classic images were taken and compared with images from the blank group.
[0137] The second group of materials were directly stained (live / dead staining, 2.5-day confocal microscopy imaging) to observe the growth of osteocytes in the middle of the scaffold. At the same time, the control group was directly stained to observe the growth of osteocytes in the middle for comparison;
[0138] The third group had the largest number of cells and the culture medium was changed to osteogenic medium and continued to be cultured without other treatments;
[0139] Day 21: Osteogenic differentiation index test: alkaline phosphatase without staining elesa test;
[0140] Antibacterial experiment: The blank group, control group, and experimental group were cultured in the same manner, and live-dead staining was performed during the culture process to observe the sterilization status; CCK-8 identification was performed after 12 hours, 1 day, and 3 days of bacterial culture, live-dead staining images were obtained, and inhibition zone experiments were performed before the animal implantation surgery began;
[0141] The experimental rabbits were randomly divided into 3 groups (no treatment group, traditional bone repair scaffold group, and ZAS group);
[0142] Establish a rabbit femoral condyle fracture model;
[0143] Adaptive feeding for 1 week, no food or drink for 6 hours before surgery;
[0144] Anesthesia was performed by intravenous injection of 3% pentobarbital (0.5 ml / kg);
[0145] After the anesthesia takes effect, the rabbit is placed in a supine position on the animal operating table and its limbs are fixed with bandages.
[0146] The lower limbs were shaved and disinfected within a 20 cm radius centered on the knee joint, and draped in a conventional manner.
[0147] Flex the knee joint and make a 5cm long paramedian incision. Dissect layer by layer and cut the lateral retinaculum.
[0148] Extend the knee and gently push the patella inward to dislocate the patella, exposing the femoral condyle, and flex the knee;
[0149] A bone drill was used to drill the ipsilateral bone just above the articular surface of the lateral femoral condyle. The ipsilateral cortical bone and internal cancellous bone were then chiseled with a bone knife, leaving the contralateral cortical bone intact. This created a 7 mm diameter, approximately 6 mm deep (to be measured) bone defect. The defect was then flushed with sterile saline until no bone debris or bone marrow remained. A ZAS / untreated / conventional bone repair scaffold of the corresponding length was then implanted. Two bone defects were prepared in the same manner on the left femur.
[0150] After flushing with dilute iodine and normal saline, the wound was closed layer by layer;
[0151] Penicillin 1.6 million UI was injected intramuscularly postoperatively;
[0152] The surgery was performed on both legs. No activity restrictions were imposed after the surgery. The animal's mental state, eating, defecation, urination, and movement of the affected limb were observed. The wound was also monitored for infection and dehiscence.
[0153] Micro-computed tomography (micro-CT) testing:
[0154] The scaffold-bone interface and surrounding bone growth were examined using high-resolution micro-CT. Four weeks after surgery, the surgical site specimen was placed in a micro-CT scanner for scanning (pixel size 19 μm, scanning voltage 70 kVp, scanning current 114 μA, integration time 250 ms). The resulting engineering file was analyzed using μCT software, using the auto-contouring function to calculate bone mass within 1 mm of the implant, assess the relative trabecular bone volume (BV / TV), and perform three-dimensional reconstruction to more intuitively observe the implant interface and surrounding bone growth.
[0155] In vivo testing of biosafety and serum biochemical testing:
[0156] Twenty-four weeks after surgery, serum was collected and creatinine (Cr) and alanine aminotransferase (ALT) were measured using ELISA kits according to the instructions to assess liver and kidney function. C-reactive protein (CRP), a marker of systemic inflammatory response, was also measured to observe whether there was a systemic inflammatory response.
[0157] Histological examination of important organs:
[0158] Twenty-four weeks after surgery, viscera (liver, spleen, kidney) and soft tissues around the implants were collected and fixed with 4% paraformaldehyde solution. The liver, spleen, kidney, and soft tissues around the implants were fixed with 4% paraformaldehyde, dehydrated, embedded, and prepared into paraffin sections. Hematoxylin and eosin staining was performed to observe whether there were obvious changes in organ structure and local inflammatory reactions around the surgery.
[0159] Statistical analysis:
[0160] Statistical analysis was performed using statistical analysis software, and the data were expressed as mean ± standard deviation (±s). The t test was used for group comparison, and P < 0.05 was considered statistically significant;
[0161] Conclusion analysis of the embodiment:
[0162] In Example 1, the performance indicators were measured and obtained: the antibacterial rate was 95%, the contact angle was 8°, the penetration rate was 9.5 μL / min, and the fitness function value was 1.24; the antibacterial rate was optimized from the initial 85% to 95%, significantly reducing the risk of postoperative infection; the contact angle was optimized from the initial 15° to 8°, reaching the super-hydrophilic standard (less than 10°), enhancing the affinity of the scaffold with body fluids / cells and promoting bone tissue regeneration; the penetration rate was increased from 7 μL / min to 9.5 μL / min, shortening the infiltration process time and improving the penetration efficiency. The whole process time was 20 hours;
[0163] In Example 2, the measured antibacterial rate was 78%, the contact angle was 20°, and the penetration rate was 4.5 μL / min. Compared with Example 1, the antibacterial rate was only 78%, which was lower than 95%, and the antibacterial performance was insufficient, and the risk of postoperative infection was increased. In addition, the contact angle of 20° was greater than 8°, and the body fluid wettability and hydrophilicity were poor, which affected cell adhesion and bone integration. At the same time, the penetration rate was only 4.5 μL / min, which was lower than 9.5 μL / min. 8 cycles were required to reach the target penetration amount, and the process time was extended by 20%.
[0164] In Example 3, the measured antibacterial rate was 82%, the contact angle was 18°, and the penetration rate was 5.2 μL / min. Compared with Example 1, the antibacterial rate was only 82%, which was lower than 95%, and the antibacterial performance was insufficient, and the risk of postoperative infection was increased. In addition, the contact angle of 18° was greater than 8°, and the sol surface was not fully extended due to the short infiltration time, resulting in poor hydrophilicity. At the same time, the penetration rate was only 5.2 μL / min, which was lower than 9.5 μL / min. 8 cycles were required to reach the target penetration amount, and the process time was extended by 20%.
[0165] In Example 4, the measured antibacterial rate was 85%, the contact angle was 15°, and the penetration rate was 5.2 μL / min. Compared with Example 1, the antibacterial rate was only 85%, which was lower than 95%, and the antibacterial performance was insufficient, and the risk of postoperative infection was increased. In addition, the contact angle of 15° was greater than 8°, and the sol surface was not fully extended due to the short infiltration time, resulting in poor hydrophilicity. At the same time, the penetration rate was only 5.2 μL / min, which was lower than 9.5 μL / min. 5 cycles were required to reach the target penetration amount, and the process time was extended by 10%.
[0166] In Example 5, the measured antibacterial rate was 90%, the contact angle was 10°, and the penetration rate was 9.0 μL / min. Compared with Example 1, the antibacterial rate of 90% was lower than 95%, and the antibacterial performance was insufficient. In addition, the contact angle of 10° was greater than 8°, indicating poor hydrophilicity. At the same time, the penetration rate was 9.0 μL / min, which was lower than 9.5 μL / min. Four cycles were required to reach the target penetration amount, and the process time was extended by 10%.
[0167] In Example 6, the antibacterial rate was measured to be 88%, the contact angle was 8°, and the penetration rate was
[0168] 9.4 μL / min; compared with Example 1, the antibacterial rate of 88% is lower than 95%, and the risk of postoperative infection is increased; in addition, the contact angle of 8° meets the super-hydrophilic standard and has good hydrophilicity; at the same time, the penetration rate of 9.4 μL / min is slightly lower than 9.5 μL / min, and 4 cycles are required to reach the target penetration amount, and the process time is extended by 10%; at the same time, the fitness function value is 0.99, which is lower than 1.24, and the hydrophilicity and blood penetration are good;
[0169] In Example 7, the antibacterial rate was measured to be 90%, the contact angle was 9°, and the penetration rate was
[0170] 9.2 μL / min; compared with Example 1, the antibacterial rate of 88% is lower than 95%, the antibacterial performance is insufficient, and the risk of postoperative infection is increased; in addition, the contact angle of 9° is slightly greater than 8°, reaching the superhydrophilic standard; at the same time, the penetration rate of 9.2 μL / min is slightly lower than 9.5 μL / min, and 4 cycles are required to reach the target penetration amount, and the process time is extended by 10%; at the same time, the fitness function value is 0.8, which is lower than 1.24, and the balance is good;
[0171] In Example 8, the measured antibacterial rate was 88%, the contact angle was 10°, and the penetration rate was 8.1 μL / min; compared with Example 1, the antibacterial rate of 90% was lower than 95%, the antibacterial performance was insufficient, and the risk of postoperative infection was increased; in addition, the contact angle of 10° was greater than 8°, which did not meet the super-hydrophilic standard; at the same time, the penetration rate was 9.1 μL / min, which was lower than 9.5 μL / min, and 4 cycles were required to reach the target penetration amount, and the process time was extended by 10%; at the same time, the fitness function value was 0.79, which was lower than 1.24, and the anti-inflammatory and sterilization properties and super-hydrophilic properties were insufficient.
[0172] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0173] The preferred embodiments of the invention disclosed above are intended only to help illustrate the invention. These preferred embodiments do not exhaust all details, nor do they limit the invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A method for preparing a zinc oxide-alumina ceramic bone repair scaffold, characterized in that: include: S1. Preparation of 3D printing powder: weighing alumina granulation powder and phenolic resin powder according to a proportion, mixing the alumina granulation powder and phenolic resin powder to obtain 3D printing composite powder; S2, forming: preparing an alumina ceramic body by subjecting the 3D printed composite powder to a selective laser sintering device; S3, degreasing and sintering: drying the alumina ceramic body to obtain a dried ceramic body, degreasing and sintering the dried ceramic body, and cooling to obtain an alumina preform; S4. Body infiltration: vacuum pressure infiltration is performed on the alumina preform using nano zinc oxide sol, and the dynamic optimization algorithm is introduced to optimize the vacuum pressure infiltration parameters to obtain a zinc oxide-alumina ceramic bone repair scaffold.
2. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 1, characterized in that: The alumina granulated powder and the phenolic resin powder are weighed in proportion, and the mixing of the alumina granulated powder and the phenolic resin powder comprises the following steps: 20-75 micron nearly spherical alumina powder and phenolic resin are selected, and after drying, alumina granulation powder and phenolic resin powder are obtained. The alumina granulation powder and phenolic resin powder are weighed according to the proportion, and the alumina granulation powder and phenolic resin powder are mixed to obtain 3D printing composite powder.
3. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 2, characterized in that: Alumina granulated powder and phenolic resin powder were weighed in a mass ratio of 0.92:0.
08.
4. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 3, characterized in that: The 3D printing composite powder is subjected to selective laser sintering equipment, comprising the following steps: The 3D printed composite powder was passed through a selective laser sintering device, wherein the operating parameters of the selective laser sintering device were a preheating temperature of 55° C., a layer thickness of 0.18±0.01 mm, a filling speed of 3850±100 mm / s, a filling power of 18 W, a contour speed of 2000±100 mm / s, and a contour power of 10 W; A gradient filling strategy was adopted to set longitudinal through-holes along the long axis of the bone in the selective laser sintering equipment, maintain the pore size at 200-500 microns, and adjust the gradient distribution of the hole spacing to obtain an alumina ceramic green body.
5. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 4, characterized in that: The degreasing and sintering treatment of the dried ceramic body comprises the following steps: The alumina ceramic body is dried to obtain a dried ceramic body, and the dried ceramic body is degreased to obtain a degreased ceramic body; a multi-stage sintering method is then used for sintering. After the sintering, the temperature is lowered to 1100° C. at a rate of 5° C.±1° C. / min, and the alumina preform is obtained by cooling.
6. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 5, characterized in that: Under nitrogen protection, the temperature was raised to 300°C at 1°C±0.1°C / min and kept at that temperature for 2 hours. The temperature was then raised to 600°C at 2°C±0.2°C / min and kept at that temperature for 30 minutes to complete the degreasing treatment.
7. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 6, characterized in that: The multi-stage sintering method comprises the following steps: During the first stage of sintering, the degreased ceramic body is kept at 600°C for 30 minutes; during the second stage of sintering, the temperature is increased to 1250°C at 8°C±1°C / min; during the third stage of sintering, the temperature is increased to 1300-1500°C at 2.5°C±0.5°C / min and kept at this temperature for 3 hours to complete the sintering process.
8. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 7, characterized in that: The vacuum pressure infiltration of the alumina preform using nano zinc oxide sol comprises the following steps: Nano zinc oxide sol is prepared, and the aluminum oxide preform is vacuum pressure infiltrated with the nano zinc oxide sol. The aluminum oxide preform is placed in a vacuum pressure infiltration device and infiltrated into the nano zinc oxide sol. The vacuum pressure infiltration parameters are as follows: vacuum negative pressure of 0.06-0.10 MPa, maintained for 1-5 minutes, and then nitrogen is introduced to increase the pressure to 0.10-0.20 MPa and maintained for 1-5 minutes.
9. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 8, characterized in that: The method of optimizing the vacuum pressure infiltration parameters by introducing the dynamic wheat optimization algorithm includes the following steps: The antibacterial rate, contact angle, and penetration rate of zinc oxide-alumina ceramic bone repair scaffolds were measured, and an objective function was established based on maximum anti-inflammatory and sterilization performance and superhydrophilic properties. The vacuum pressure infiltration parameters include vacuum negative pressure, pressurization pressure, infiltration time and number of cycles, which constitute a vacuum pressure infiltration parameter combination; the objective function is used as a fitness function, and the process of finding the optimal fitness function value is regarded as the process of finding the optimal vacuum pressure infiltration parameter combination; A search space is set, in which there is an oat population, and each oat individual in the oat population is regarded as a vacuum pressure infiltration parameter combination; Initialize the oat population and calculate the biological parameters of the oat population; The oat population enters the exploration phase. After the oats fall, they spread. The positions of individual oats in the oat population are updated. The fitness function values corresponding to the individual oats in the oat population are calculated to obtain the current vacuum pressure infiltration parameter combination. The oat population enters the development phase, and the current vacuum pressure infiltration parameter combination is updated by simulating the propagation process; When the oat population does not encounter any obstacles during its propagation, the Lévy flight and tumbling mechanism is introduced to update the position of individual oats according to the biological parameters of the oat population. When the oat population encounters an obstacle during its propagation, the projectile motion model is introduced to update the individual oat positions again; Until the current number of iterations reaches the maximum number of iterations, the iteration is stopped and the final oat population is obtained; The oat individual corresponding to the best fitness function value is found in the final oat population to obtain the optimized vacuum pressure infiltration parameters.
10. The method for preparing a zinc oxide-alumina ceramic bone repair scaffold according to claim 9, characterized in that: The steps of obtaining the zinc oxide-aluminum oxide ceramic bone repair scaffold include: The optimized vacuum pressure infiltration parameters include optimized vacuum negative pressure, optimized pressurization pressure, optimized infiltration time and optimized number of cycles. The alumina preform is vacuum pressure infiltrated according to the optimized vacuum pressure infiltration parameters to obtain an infiltrated repair scaffold, which is then dried and low-temperature cured to obtain a zinc oxide-alumina ceramic bone repair scaffold.
Citation Information
Patent Citations
Prepn process of multifunctional honeycomb ceramic filter element
CN101088959A
Laser zone-selection rapid forming method for complex-phase ceramic casting mold and product thereof
CN109734425A
Porous ceramic atomizing core and preparation method thereof
CN113292354A
Gradient impedance high-temperature ceramic wave-absorbing material based on 3D printing technology and preparation method of gradient impedance high-temperature ceramic wave-absorbing material
CN117430429A
High-porosity and high-strength aluminum oxide ceramic and 3D printing preparation method thereof
CN118047626A